Kiribati : 2009 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Kiribati. (IMF Staff Country Reports; Country Report ;, 2009)
This 2009 Article IV Consultation highlights that inflation in Kiribati increased to about 19 percent by end-2008, largely reflecting higher food prices. The current account deficit was broadly unchanged in 2008. Structural reforms are under way, although the pace has been limited by capacity constraints. Executive Directors have welcomed the recent improvement in economic activity. They have also welcomed the planned review and reform of public enterprises as critical to promoting private sector development, and to boosting the growth potential.